2005
DOI: 10.1111/j.1365-2443.2005.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the taxilin family with the nascent polypeptide‐associated complex that is involved in the transcriptional and translational processes

Abstract: α α α α -Taxilin is a novel binding partner of the syntaxin family, which is implicated in intracellular vesicle traffic. We have here found that α α α α -taxilin interacts with the nascent polypeptide-associated complex (NAC), which is involved in transferring growing nascent polypeptide chains to appropriate co-translationally acting factors. NAC is composed of two subunits, α α α α -and β β β β NACs. Both these subunits bound to α α α α -taxilin through its C-terminal coiled-coil region in dose-dependent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 25 publications
(52 reference statements)
5
35
1
Order By: Relevance
“…37 Furthermore, aNAC was reported to interact with g-taxilin, which inhibits ATF4-mediated transcription. 18,19 In this study, we showed that aNAC ablation by the RNA interference resulted in the upregulation of ATF4 and downregulation of g-taxilin (Figure 4a), consistent with the previous findings. Therefore, these studies imply that aNAC and eIF2a might coordinately regulate transcriptional and translational responses of the cell to hypoxia, thereby determining the fate of the hypoxic cell.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…37 Furthermore, aNAC was reported to interact with g-taxilin, which inhibits ATF4-mediated transcription. 18,19 In this study, we showed that aNAC ablation by the RNA interference resulted in the upregulation of ATF4 and downregulation of g-taxilin (Figure 4a), consistent with the previous findings. Therefore, these studies imply that aNAC and eIF2a might coordinately regulate transcriptional and translational responses of the cell to hypoxia, thereby determining the fate of the hypoxic cell.…”
Section: Discussionsupporting
confidence: 80%
“…Previous reports have shown that g-taxilin is a regulator of ATF4 activity and interacts with aNAC. 18,19 Therefore, we assessed g-taxilin protein Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these findings suggest that the taxilin family could play an important role in the process of translation through interaction with NAC, as well as transcription through interaction with αNAC alone (44). Correct transmission of genetic information through both transcriptional and translational processes is important for normal cell function.…”
Section: Referencesmentioning
confidence: 99%
“…On the other hand, it has been recently reported that α-taxilin interacts with the nascent polypeptide-associated complex (NAC), mainly through its alphasubunit (αNAC) (44). There is increasing evidence binding protein involved in intracellular vesicle trafficking (26).…”
Section: Transcription and Translationmentioning
confidence: 99%
“…The polyclonal anti-human ·-taxilin antibody raised in a rabbit was used for immunohistochemistry, as previously described (12).…”
Section: Methodsmentioning
confidence: 99%